Edukasi Wawasan Kebangsaan: Tanggung Jawab Sosial Umat Kristen Dalam Pemilu 2024 - Setiawan, Tjutjun; Stefanus, Tonny Andrian; Rachmat, Ronald; Kurniawan, Andreas; Simon, Simon (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2024)
Indonesia, as a democratic nation, regularly holds elections to select legislative and executive members. The 2024 elections mark a significant moment, especially for Christians, who have a social responsibility to actively participate. This participation is crucial, as the election results will greatly impact the lives of the people and the nation. Hence, this community service initiative aims to increase Christian participation in the 2024 elections and raise awareness about their social responsibilities within the democratic context. The activity was held through a seminar at GKPB Fajar Pengharapan, Bandung, featuring speakers from diverse backgrounds. The methods used include presentations, discussions, and QA sessions, supported by descriptive qualitative data from various literature sources. The goal is to raise awareness among Christians about the importance of participating in the 2024 elections and understanding their social responsibilities. The education effort also targets first-time voters (millennials) to help them make informed voting decisions. This educational initiative stimulates awareness and commitment among Christians to actively participate in the 2024 elections. With a better understanding of their roles and social responsibilities, it is hoped that Christians will contribute to fair and honest elections and elect leaders capable of bringing positive change to Indonesia.Keywords: church; politics; social responsibility Christians; electionsAbstrak Indonesia sebagai negara demokrasi, rutin mengadakan pemilihan umum untuk memilih anggota legislatif dan eksekutif. Pemilu 2024 merupakan momentum penting, terutama bagi umat Kristen yang memiliki tanggung jawab sosial untuk berpartisipasi aktif. Partisipasi ini sangat penting mengingat hasil pemilu berdampak besar pada kehidupan masyarakat dan negara. Itulah pentingnya PkM ini untuk meningkatkan partisipasi umat Kristen dalam Pemilu 2024 dan memberikan pemahaman tentang tanggung jawab sosial mereka dalam konteks demokrasi. Kegiatan ini dilaksanakan melalui sarasehan di GKPB Fajar Pengharapan, Bandung, dengan menghadirkan narasumber dari berbagai latar belakang. Metode yang digunakan adalah penyampaian materi, diskusi, dan tanya jawab, yang didukung oleh data kualitatif deskriptif dari berbagai literatur. Membangkitkan kesadaran umat Kristen tentang pentingnya partisipasi dalam Pemilu 2024 dan memahami tanggung jawab sosial mereka. Edukasi ini juga ditujukan untuk pemilih pemula (milenial) agar mereka dapat menggunakan hak pilih dengan bijaksana. Kegiatan edukasi ini merangsang kesadaran dan komitmen umat Kristen untuk berpartisipasi aktif dalam Pemilu 2024. Dengan pemahaman yang lebih baik tentang peran dan tanggung jawab sosial mereka, diharapkan umat Kristen dapat berkontribusi dalam pemilu yang jujur dan adil, serta memilih pemimpin yang mampu membawa perubahan positif bagi bangsa Indonesia.Kata Kunci: gereja; politik; tanggung jawab sosial; umat Kristen; pemilu